Financial market in the context of digital innovation: implications for marketing practices - Sukach, O.; Savchenko, S. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
In the current context of financial services transformation driven by rapid technological development, increasing competition, and changes in consumer behavior, marketing strategy requires a profound rethinking and adaptation to the digital paradigm. This article explores the key drivers of innovative change: FinTech developments, mobile platforms, artificial intelligence, blockchain, big data, and algorithmic marketing. It examines the features of integrating digital tools into the marketing policies of financial institutions, including the personalization of customer experience, automation of communication processes, development of omnichannel platforms, and the application of customer behavior analytics. Special attention is given to the construction of a marketing strategy for digital innovations based on the concepts of value-oriented marketing, digital adaptation, and cross-platform promotion of financial products. Digital innovations not only open up new opportunities for the promotion of financial services but also require marketers to acquire new competencies and adapt to shifts in consumer behavior. The article proposes an original model of strategic management for marketing innovations, which considers the stages of development, implementation, and evaluation of the effectiveness of digital solutions. The study also highlights current challenges such as distrust towards new financial services, cybersecurity risks, the complexity of the regulatory environment, and the uneven level of digital literacy among clients. The conclusion emphasizes that an effective marketing strategy in the digital financial environment should combine innovative technologies with ethical approaches to data collection and usage, thereby ensuring customer trust and market stability. The theoretical and practical insights presented in the article may serve as a foundation for developing effective marketing policies for domestic financial institutions amid the digital transformation of the economy.